Writing Portugal in foreign language: Oh! Lusitania, by Rui Pires Cabral - Pimenta, Tamy de Macedo (2017)
Reviewed book:PIRES CABRAL, Rui. Oh! Lusitania. Lisboa: Paralelo W, 2014.---DOI: http://dx.doi.org/10.21881/abriluff.2016n17a387